PHOTOMAGNETIC CONVERTER - Onarkulov Karimberdi Egamberdievich; Yuldashev Shohjahon Abrovich; Yuldashev Abror Abduvositovich; Yuldasheva Shahrizoda Abrorjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
An optoelectronic miniature device for obtaining large electric fields from solar radiation using the magnetic field of various natural and artificial sources has been developed and studied. The design of the technology for manufacturing epitaxial thin films is proposed. The device does not require a separate external power supply to operate. This optoelectronic converter ensures the autonomy and independence of the system. Such photo magnetic converters are used as photovoltaic stimulators of various chemical and technological processes and means of sorting complex molecular flows.